2016
DOI: 10.1111/bjh.14345
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian‐target of rapamycin inhibition with temsirolimus in myelodysplastic syndromes (MDS) patients is associated with considerable toxicity: results of the temsirolimus pilot trial by the German MDS Study Group (D‐MDS)

Abstract: The mammalian-target of rapamycin (also termed mechanistic target of rapamycin, mTOR) pathway integrates various pro-proliferative and anti-apoptotic stimuli and is involved in regulatory T-cell (TREG) development. As these processes contribute to the pathogenesis of myelodysplastic syndromes (MDS), we hypothesized that mTOR modulation with temsirolimus (TEM) might show activity in MDS. This prospective multicentre trial enrolled lower and higher risk MDS patients, provided that they were transfusion-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Rapamycin and rapalogues are, to date, the most powerful autophagy enhancer agents, although they are loaded with frequent and unwanted effects that currently limit their use to few selected conditions, such as anti-cancer and anti-transplant rejection therapies [244,245]. The recent great surge of scientific interest in autophagy as an anti-aging strategy stimulated the identification of molecular pathways that control the process and led to the definition of new targets for less toxic molecules to be used for long periods under non-life-threatening conditions.…”
Section: Future Development Of Autophagy Enhancers In Neurodegenementioning
confidence: 99%
“…Rapamycin and rapalogues are, to date, the most powerful autophagy enhancer agents, although they are loaded with frequent and unwanted effects that currently limit their use to few selected conditions, such as anti-cancer and anti-transplant rejection therapies [244,245]. The recent great surge of scientific interest in autophagy as an anti-aging strategy stimulated the identification of molecular pathways that control the process and led to the definition of new targets for less toxic molecules to be used for long periods under non-life-threatening conditions.…”
Section: Future Development Of Autophagy Enhancers In Neurodegenementioning
confidence: 99%
“…Platzbecker et al ( 43 ) treated 19 MDS patients with SRL as a single agent, and demonstrated that SRL might have some activity in patients with more advanced MDS but lacked efficacy in low-risk MDS patients. Martin et al ( 44 ) treated 20 MDS patients with temsirolimus at a weekly dose of 25 mg; however, only four (20%) reached the response assessment after 4 months without hematological improvement. Based on these this response assessment, they concluded that Temsirolimus has no beneficial effects in elderly MDS patients.…”
Section: Applications Of Mtori In Hematological Malignanciesmentioning
confidence: 99%
“…7,8 PEM was administered according to guidelines for patients with unresectable melanoma at a dose of 2 mg/kg IV over 30 minutes every 3 weeks.…”
Section: Clinical and Molecular Response Assessmentmentioning
confidence: 99%